P125 Non-invasive assessment of ventilation distribution in infants using electrical impedance tomography (EIT). (16th November 2010) - Shah, P A; Shannon, H; Hoo, A-F; Ahmed, D; Chudleigh, J; Stocks, J
Abstract : Background: Early detection of lung disease in conditions such as cystic fibrosis (CF) is vital to maximise lung health but lung function tests (LFT) during the 1st year of life are limited to a few specialised centres. Electrical Impedance Tomography (EIT) provides a novel non-invasive technique for measuring breathing patterns and regional ventilation but its use has generally been restricted to anaesthetised or ventilated subjects in intensive care.1 2 Aim: To assess the feasibility and potential usefulness of EIT for monitoring changes in breathing pattern and ventilation distribution in spontaneously breathing sleeping infants. Methods: Simultaneous recordings of EIT (Goe-MF II EIT system) and changes in tidal volume using a pneumotachograph (PNT) were made in the supine position in infants undergoing standard LFT under chloral sedation, before and after application of face mask and PNT, and during tidal breathing (TB) vs passive lung inflations (PLI) to 30cmH2 O. Results: To date, paired data have been obtained from 9/10 infants in whom measurements were attempted (aged 3–12 months: five=CF and four=healthy controls, one technical failure of EIT). Application of the face mask resulted in a mean (range) 27 (12–39)% increase in impedance. Compared with TB, PNT volume increased by mean (SD) 127 (20)% during PLI, which was accompanied by a 152 (22)% increase in impedance. During TB, ventilation was relatively evenly distributed between left (L) and right (R) lung, mean (SD) L/R:1.09 (0.22) and, as in adults, was preferentially distributed to the dependent (dorsal) lung (dorsal/ventral (D/V):1.36 (0.29)). During PLI, there was a significant shift in ventilation distribution to the left and ventral portions of the lung (mean (95% CI) L/R:1.29 (1.24; 1.35); D/V:0.89 (0.71;1.06)) (Abstract P125 Figure 1 ). Data collection is continuing. Conclusions: These results suggest that EIT maybe a useful non-invasive method of monitoring changes in breathing pattern and ventilation distribution in spontaneously breathing infants. Despite suggestions that distribution of ventilation differs in infants, the preferential distribution to the dependent lung during tidal breathing mimics that seen in adults. Improvements in software and equipment will be required prior to routine applications.